'Zion, Memory and Hope of All Ages': Nina Davis Salaman's Romantic-Zionist Poetry. (4th February 2021) - Devine, Luke
Abstract: This article analyses the romantic-Zionist poetry of Nina Davis Salaman, contextualising it alongside other fin-de-siècle Zionist poets to argue that she too similarly adopted bibliocentric, prophetic, and diasporic perspectives, particularly themes associated with the medieval Andalusian poetry of Judah Halevi. In doing so, Salaman, much like other Anglo-Jewish women writers, defined her own subjectivity in the context of nostalgic, romanticising religious and nationalistic discourses. However, uniquely, Salaman's poetry adopts not only the themes of medieval Andalusian verse yearning for Zion-Jerusalem and the land of Israel, but also, as she put it, its diasporic 'clothing of metre and rhyme'. Indeed, Salaman's romantic poetry is populated with intertextual links recalling the biblical Prophets and Halevi's exilic poetry, which offer historical and scriptural substantiation to support contemporaneous Zionist discourses. Songs of Many Days draws equally on her underlying belief that 'metre and rhyme', including in her own poetry, are a feature of diasporic existence.